Indicators of cumulative disability due to malignant neoplasms of the brain for 2016-2021 - Natalia S. Zapariy; Olga I. Potapenko; Aleksandr V. Vyalov (ZAO "Consilium Medicum", 2023)
Background. One of the major issues of disability is improving the medical rehabilitation system for patients and disabled people due to malignant neoplasms of the brain. It is important to study the patterns of disability to develop effective medical and social rehabilitation methods for disabled people. Aim. To study the cumulative disability of the adult population due to malignant neoplasms of the brain in Moscow for 20162021 to develop measures for the prevention of morbidity and disability of this population, recommendations for improving comprehensive medical and social rehabilitation at all stages, and the provider of rehabilitation services. Materials and methods. It was a continuous study. The study included patients aged 18 years and older, examined and re-examined at the Bureau of Medical and Social Expertise due to malignant brain neoplasms in Moscow for 20162021. Results. Cumulative disability due to malignant neoplasms of the brain among the adult population of Moscow for 20162021 showed an increase in the total number of disabled people with a predominance of persons repeatedly recognized as disabled, the predominance of disabled people of working age with a tendency to rate increase, the predominance of malignant neoplasms of the brain (C71), frontal lobe (C71.1), and overlapping lesions of brain (C71.8); III disability category and males prevailed.